Study of odor pollution by x slaughterhouse waste in Central Java 2021 - Pangalinan, Gabriella Gitamega; Sarto; Wiranto (BKM Public Health and Community Medicine, 2022)
Purpose: Bad waste management causes the slaughterhouse's environment to look unsightly and unpleasant. This research aimed to evaluate the factors that cause odor pollution by X Slaughterhouse waste. Methods: This qualitative research used a case study approach. Informants were recruited through purposive sampling. The primary informants were six people who lived or worked around slaughterhouses. The supporting informants were the Head of the Slaughterhouse Division, the slaughterhouse's daily waste officer, and the Environmental Service's Head of Impact Assessment and Waste Management Division. Research conducted in Central Java. Open Code 4.02 was used to analyze the qualitative data. Results: Overall, the slaughterhouse's facilities were not appropriate for the requirements in SNI 01-6159-1999. The odor pollution caused by the waste discharged into the environment without proper management was supported by the results of the BOD level test from the slaughterhouse's sewers, 261,5 mg/L. The most significant discharge in the slaughterhouse's sewer was when the slaughterhouse had been cleaned, 0,137 m3/s, and the most minor discharge was during the slaughter activity, 0,006 m3/s. The slaughterhouse was disinfected after slaughter activity to protect the environment from slaughterhouse waste. Meanwhile, the Environmental Service has not made any specific efforts. Conclusion: Lack of adequate waste management facilities caused the odor pollution. It is necessary to stipulate waste management guidelines, supervise the slaughterhouse's waste management, and coordinate relevant services to monitor and evaluate it. The following researchers can observe using all the requirements in SNI 01-6159-1999.